A concepção de paisagem de professores de geografia em escolas do município de Parnamirim (RN) - Almeida, Alberto Alexandre Lima de (2013)
This work is an exploratory study based on the principles of qualitative research aiming at the conception of landscape by Geography teachers in the city of Parnamirim (RN), as well as the pedagogical implications originated from such conceptions on the formation of students. In order to start our investigative process, we used, as theoretical and methodological reference, some principles of historical and dialectical materialism by Triviños (2007) and historical cultural approach of education by Freire (1987; 1996) e Vygotsky (1993; 2001; 2007), as well as the meaning of conception by Morin (1996) and Ferreira (2007) and the critical approach of geography by Moraes (2005), Santos (1988; 2004; 2006) and Silva (1989; 2010). Also, we used oral history as a research technique such as Moraes (2004), Bertaux (2010), Ferraroti (2010) and Nóvoa (2010) and semi-structured interviews as data collection tools. Our empirical reference is made of four teachers working in four different public schools in the city mentioned above, providing the needed data to start our research. The objective of such interviews is not the verification of the teachers‟ practice in class or outside them, but it highlights the transitoriness of the evidences mentioned in the research. Thus, we conclude that the conception of landscape mostly accepted by the teachers, once it is a process built along their lives and surrounded by their pedagogical practice, prioritizes the visual and morphological aspects and the sentimental livings related to the conception which is situated in a descriptive level of conception. Effectively, the pedagogical implications of these conceptions at school point to a materialization of geography teaching centered on the non-critical reproduction of school subjects which very little instigate the learners to process, via dialogicity, the re-significations of their essential and multiple attributes despite the several attempts and possibilities of some theoretical and methodological renovations on the application of geographical knowledge about landscape, expressed on the report of the interviewees